Large-scale preparation of phage DNA - Morrey, John D. (Utah : Taped Technologies, 1988)
Shows the preparation of large quantities of phage DNA by first infecting a liquid suspension of bacteria with the phage.
Copy available in DVD format
Keywords: Bacteriophages